Determinants of Smoking Behavior in Adolescents - Titik Sumiatin; Wahyu Tri Ningsih; Su'udi Su'udi; Aby Yazid Al Busthomy Rofi’i (Journal of Ners and Midwifery, 2022)
Smoking behavior as one of the riskiest behaviors carried out by teenagers has always been a problem throughout the ages. As long as the root cause is still there and supported by various policies that are in favor of the owners of the cigarette industry, during that time the problem of smoking will always exist. One of the districts in East Java with the highest number of smokers is Tuban. This study aims to determine what factors are the most dominant influencing adolescent smoking behavior in Tuban Regency. The population in this study were junior high school youth in the district of Tuban, both smokers and non-smoker. The design in this study was analytic with a Cross-Sectional approach. The population was junior high school youth, both male and female, totaling 2,866, with a sample size of 287 using purposive sampling. The independent variables in this study were gender, puberty status, self-esteem, motivation, health status, work, economy, environment, friends, family, models/role models. Data was collected using a questionnaire compiled by the research team using the Pender Model theory approach. The collected data was analyzed by logistic regression test. The results showed that most of the adolescents did not smoke by 98.61%, more than half of the adolescents were female (58.89%), almost all of them had experienced puberty (96.17%), most of them had negative self-esteem (88.50%), all of whom stated that smoking did not motivate to do activities, all of them stated that they did not smoke during their illness, almost all of them did not have a side job (97.56%), more than half of the parents had income above the minimum wage (53.31%), almost all stated that the environment did not affect smoking behavior (99.30%), almost all stated that friends did not influence smoking behavior (98.95%), almost all stated that family did not influence smoking behavior (99.65%), and almost all stated that their model/role model did not affect smoking behavior (99.65%). Based on the results of statistical tests, it was found that all factors had a significance > 0.05 so that there were no factors that significantly influenced smoking behavior in adolescents or in other words there was no dominant factor that significantly affected smoking behavior in adolescents in Tuban district. For related parties such as schools, the health office, health education participate in maintaining and continuing to improve education to adolescents about the dangers of smoking so that adolescents do not engage in behaviors that are more risky to health than the benefits obtained.